Primary Education Undergraduates’ Awareness and Perception on the Utilization of Open Educational Resources for Learning in University of Ilorin - Omolafe Ebenezer (Indonesian Journal of Primary Education, 2022)
The purpose of Primary Education Undergraduates’ Awareness and Perception on the Utilization of Open Educational Resources for Learning in University of Ilorin.The use of Open Educational Resources (OER) in this present dispensation is considered to be very essential. It is indicated that students use a limited range of technologies for learning, with established technologies such as VLEs, Google and Wikipedia being the most frequently used, based on the previous findings it is observed that utilization of OER is not common among primary education undergraduates. Therefore, this study investigated the awareness and perception on the utilization of OER for learning among primary education undergraduates in University of Ilorin.  The study adopted the descriptive research of survey type. This study was limited to the primary education undergraduate students in Adult and Primary Education Department, University of Ilorin. 150 undergraduate were randomly selected from the department. Structured questionnaires was used to elicit response from the respondents. The finding of this study shows that undergraduate students are aware of OERs learning tools. Primary education undergraduate students’ perception towards OERs tool for learning is positive, there are factors inhibiting effective use of OER for learning among students, undergraduate students used OERs site for learning, and there was no significant difference between male and female undergraduates’ perception of OER tools for learning. Based on the findings of this research, the following recommendation were made. Lecturers should endeavor to put their scholarstic publications in the public domain of their institutions, as this will help student layhands on more quality materials and the government should provide fund to ensure the stability of OER movement.